Penerapan Interactive Multimedia untuk Perangkat Ajar Persiapan Toefl Berbahasa Indonesia - Arifin, Yulyani; Widjaja, Nicolas Willianto; Awang, Nicholas Kurnia; Irwan, Stefanus Sadryan (Bina Nusantara University, 2014)
One of added values to compete in work and business is mastering English’s Language. To support the needs of an online teaching tool that can be accessed anywhere and is easy to use, an online teaching tool that uses Indonesian is made with an attractive multimedia display so that users do not feel bored and can monitor the development of the value achieved. The material presented is based on the structure tested in TOEFL. The method used in designing these applications is the waterfall method, ranging from data collection through questionnaires and comparative analysis of similar applications and then proceed with the design and development of applications and user satisfaction evaluation. It is expected that these applications can help in improving the English language proficiency as measured by TOEFL score achieved.